Implementing the international exercise guidelines to improve the functional independence among the chronic spinal cord injury patients: A randomized controlled trial - Nurul Hanifah; Martha Kurnia Kusumawardani; Lydia Arfianti; Nur Sulastri; Inggar Narasinta; Dewi Poerwandari (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: This research investigated the effectiveness of a modified exercise program in accordance with international spinal cord injury (SCI) exercise guidelines for improving functional independence in individuals with chronic SCI. Methods: A randomized controlled trial with a pre–post assessment design. Chronic SCI patients were allocated to either the intervention or control group. The intervention group participated in a 12-week combined aerobic and resistance training program. Functional independence was measured using the Spinal Cord Independence Measure (SCIM-III) at baseline and post-intervention. Results: Participants of intervention showed statistically significant improvement in functional independence (SCIM-III scores 79.25 ±19.6 to 86.0±17,8 p=0.018; effect size d = 0,84). The control group showed no meaningful change (56.38 ± 24.48 to 56.88 ± 23.73, p=0.848). Between-group comparison confirmed a significantly greater gain in the intervention group (Δ6.75 ± 6.79 vs. 0.5 ± 7.09, p=0.014; effect size 0.9). No severe adverse events were reported. Conclusion: A working translation of the International SCI Exercise Guidelines has been tested in Indonesia, showing clear gains in daily living skills. Because these results match global findings, adding planned physical activity to spinal cord injury recovery may work well even where resources are limited.